PENURUNAN TEKANAN DARAH DENGAN PENERAPAN TERAPI RENDAM KAKI MENGGUNAKAN AIR HANGAT PADA PASIEN HIPERTENSI DI RUANG RAWAT INAP RSUD KARAWANG - Grace Evelyn,; Dina Hartini, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Hypertension is a condition of increasing systolic and diastolic blood pressure, where systolic is more than equal to 140 mmHg and diastolic is more than equal to 90 mmHg. Patients with hypertension who do not take treatment will increase the occurrence of complications including stroke, heart disease, vision problems, and kidney disease. One of the complementary therapies that can lower blood pressure is warm water foot soak therapy. The aim of the intervention was to determine the effectiveness of warm water foot soak therapy on reducing blood pressure in hypertensive patients. Hypertension is a disease of the heart and blood vessels which is characterized by increased blood pressure. Efforts to overcome hypertension can be done with pharmacological and non-pharmacological therapy. One of the non-pharmacological therapies that can reduce blood pressure is warm water foot soak therapy. This study aims to determine the effect of warm water foot soak therapy on reducing blood pressure in hypertensive patients. The design of this research uses Quasy Experiment, namely pre-test and post-test without control. The population in this study were residents who suffer from hypertension. The sampling technique used a total sampling technique with a total sample of 20 people. The research instrument used an observation sheet for measuring blood pressure and a checklist sheet for administering warm water foot soak therapy. Data analysis used the Paired T Test. The results of the study obtained a p value of 0.005, meaning that there was a significant effect of warm water foot soak therapy on lowering blood pressure in hypertensive patients. Warm water foot soak therapy can be used as a non-pharmacological therapy to reduce blood pressure in people with hypertension